2006
DOI: 10.1188/06.onf.1109-1116
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Life and Health Status of Dyads of Women With Lung Cancer and Family Members

Abstract: Additional study is needed to identify family members at risk for diminished QOL and with compromised health status because these factors might affect ability to support patients with lung cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
25
1
3

Year Published

2008
2008
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 50 publications
0
25
1
3
Order By: Relevance
“…Despite this change, most studies of symptoms and/or QoL in patients with LC are based on selected populations predominantly consisting of white, middle-income men with advanced LC [2]. Sarna's work on women with LC provides a notable exception [8][9][10][11][12][13]. Existing studies examining differences in symptom experience between women and men with LC are generally crosssectional, with inconclusive findings [14,15].…”
Section: Introductionmentioning
confidence: 92%
“…Despite this change, most studies of symptoms and/or QoL in patients with LC are based on selected populations predominantly consisting of white, middle-income men with advanced LC [2]. Sarna's work on women with LC provides a notable exception [8][9][10][11][12][13]. Existing studies examining differences in symptom experience between women and men with LC are generally crosssectional, with inconclusive findings [14,15].…”
Section: Introductionmentioning
confidence: 92%
“…34,68,69 The limited body of research that is available has shown that more than a third of spouses of lung cancer patients exhibit significant distress 40,70 and lower levels of QoL than the general population. 71 Persson et al 72 compared health-related QoL (HRQoL) in significant others of patients dying from lung cancer, with a general population sample. Further, they explore the course of HRQoL from diagnosis (T1), at a time point close to the patient's death (T2), and 6 months after the patient's death (T3).…”
Section: The Impact On Carersmentioning
confidence: 99%
“…20,21,22 Both the patient and the next of kin are dependent on each other"s life situations and quality of life. 21,22,23 The next of kin have a higher quality of life than those with lung cancer, but this quality of life is not only affected by the disease of the patient, but also by the health status of the next of kin. 23 The next of kin want to feel comfortable with assistance and that they have done what is necessary.…”
mentioning
confidence: 99%
“…21,22,23 The next of kin have a higher quality of life than those with lung cancer, but this quality of life is not only affected by the disease of the patient, but also by the health status of the next of kin. 23 The next of kin want to feel comfortable with assistance and that they have done what is necessary. They do not want to feel guilt due to not being a good next of kin or informal carer, or that they have been using the term "burden" in relation to their ill relative.…”
mentioning
confidence: 99%